The Influence of Green Work Environment and Mental Health on Work Productivity Moderated By Work Quality in Bekasi City Land Office Employees - Fifrianto, Andika Bayu; Razak, Ismai; Irawan Noor, Muhammad (Krisnadwipayana International Journal of Management Studies, 2024)
This study aims to analyze the influence of Green Work Environment and Mental Health on Work Productivity, with Work Quality as a mediating variable among employees at the Land Office of Bekasi City. The sample consists of 104 employees, and data was collected through a Google Form questionnaire. Data analysis was performed using SPSS and path analysis to identify the direct and indirect relationships between the variables. The results show that the Green Work Environment has a positive and significant impact on Work Productivity both directly and through the mediation of Work Quality, with a direct regression coefficient of 0.512 and an indirect effect of 0.360. Similarly, Mental Health positively influences Work Productivity, with a direct regression coefficient of 0.334 and an indirect effect through Work Quality of 0.235. Work Quality is proven to be a significant mediating variable in enhancing Work Productivity. The combined influence of the Green Work Environment and Mental Health on Work Productivity through Work Quality strengthens the positive relationship between these variables. The study concludes that improving the Green Work Environment and focusing on Mental Health can enhance Work Quality, ultimately increasing employees' Work Productivity. Therefore, organizations are advised to implement strategies that focus on developing a healthy and environmentally friendly work environment while supporting employees' mental well-being